Filling of simulated lateral canals with gutta percha or resilon when using thermomechanical compaction - Sant'Anna-Júnior, Arnaldo [UNESP]; Tanomaru Filho, Mario [UNESP]; Duarte, Marco Antônio Hungaro; Silva, Guilherme Ferreira da [UNESP]; Bosso, Roberta [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP] (Wolters Kluwer, 2014)
Aims: To evaluate the filling of simulated lateral canals with gutta-percha or Resilon when using thermomechanical compaction. Setting and Design: Forty-five human single-rooted teeth were subjected to tooth decalcification and clearing. Materials and Methods: After root canal preparation, artificial lateral canals were made at 2, 5, and 8 mm from the working length (WL), corresponding to the apical, middle, and cervical thirds, respectively. The specimens were divided (n = 15) according to the filling material: Dentsply gutta-percha (GD), Odous gutta-percha (GO), and Resilon cones (RE). Root canals were obturated by thermomechanical compaction using a #45 compactor and no sealer. Lateral canals were analyzed by digital radiography and digital images after tooth decalcification and clearing using the Image Tool software. Statistical Analysis Used: Data were subjected to the Kruskal-Wallis and Dunn tests at 5% significance. Results: In the coronal third, RE and GO presented more filling ability than GD (P < 0.05). In the middle and apical thirds, RE presented the best results. Conclusions: Resilon demonstrated filling ability as material for root canal obturation by using thermomechanical compaction.
Keywords: Gutta-percha; resilon; root canal filling; simulated lateral canals; thermomechanical compaction